Efficacy of Bupivacaine Inferior Alveolar Nerve Block Versus Intravenous Use of Tramadol for Postoperative Pain Control in Mandibular Parasymphysis Fractures - Shehryar Alam Khan, Gulraiz Zulfiqar, Ayesha Binte Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most crucial parts of any operation is postoperative monitoring and management. Numerous clinical strategies for administering analgesic drugs have been developed to reduce postoperative pain in patients. High opioid doses before, during, and after surgery might cause respiratory depression, sleepiness, nausea, vomiting, itching, difficulties urinating, and ileus. Most surgeries cause maxillo-mandibular fixation (locked jaw). In the early postoperative period, ventilatory depression and vomiting are common that’s why this study focuses on the two types of drug intervention and measures the effects. Objective: To evaluate the efficacy of bupivacaine inferior alveolar nerve block vs intra-venous tramadol (opioid) in postoperative pain control. Study Design: Prospective, randomized control trial Study Setting: The study was conducted in Jinnah Hospital, Lahore from 6 April 2022 to 6 October 2022. Methodology: The non-probability sampling technique was used to recruit the patients. Patient aged between 18 – 40 years with simple mandibular parasymphyis fracture was included in the study. However, patients with diabetes, ischemic heart disease & bone diseases were excluded from the study. The patients were divided into two groups. One group received bupivacaine while the other group received tramadol (opioid). The pain of the patient was calculated using the Visual Analog Scoring system. The frequency of pain was recorded postoperatively between 0-3hrs, 3-6hrs, 6-12hrs, and 12-24hrs. The data were analyzed by using SPSS version 22. Results: Fifty-two patients were recruited in this trial and randomly assigned to the bupivacaine group and tramadol group, there were no significant differences between the two groups in terms of demographic data including age, gender, BMI and mean operation time (P>0.05) as shown in table 1. The Visual Analog and Category Pain Scale (VAS) significanlty reduced in both the groups. The more decline in pain was observed from 12hrs to 24hrs in bupivacaine group from 4.46±0.64 to 2.27±1.00 respectively. In addition, a repeated-measures ANOVA was utilized to evaluate the VAS ratings between the two groups, revealing that the VAS values in the bupivacaine group were considerably lower than those in the tramadol group 16 and 24 hours after surgery (P=0.001 and P=0.000, respectively). Practical implication: The study’s justification is the dearth of local or regional information on this topic. Therefore, the objective of this research was to evaluate the effectiveness of tramadol intravenously against bupivacaine inferior alveolar nerve block for postoperative pain control in mandibular parasymphysis fractures. Conclusion: In conclusion, 2mL.5% Injection Bupivacaine (1:200000) administered at the fracture site in the mandibular parasymphysis fractures area post-operation relieved somatic wound pain better than tramadol without major side effects. Thus, local infiltration of bupivacaine over the section incision is recommended for safe and efficient post-operative pain. Keywords: Bupivacaine, Tramadol, Mandibular Parasymphysis Fractures, Alveolar Nerve Block